2012
DOI: 10.2150/jlve.36.16
|View full text |Cite
|
Sign up to set email alerts
|

Daylighting and Its Impact on Depth Perception in a Daylit Space

Abstract: Visual perception within a daylit environment changes according to spatiality, sky conditions, time, and the point of observation. This paper focuses on the complex interrelationships among the architectural configuration of skylights, luminance distribution patterns resulting from changing sky conditions, and the perception of spatial depth. This study employed lighting simulation techniques that incorporate physically based rendering and perceptually based tone mapping to generate a pictorial environment. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…The authors concluded that perspective cues might be more important to be included in virtual environments than other pictorial depth cues. Tai [2012] employed various lighting conditions and found a tendency for longer distance estimates in conditions with lower luminance contrast between target and background. However, the author did not report any statistical tests.…”
Section: The Availability Of Pictorial Depth Cuesmentioning
confidence: 99%
“…The authors concluded that perspective cues might be more important to be included in virtual environments than other pictorial depth cues. Tai [2012] employed various lighting conditions and found a tendency for longer distance estimates in conditions with lower luminance contrast between target and background. However, the author did not report any statistical tests.…”
Section: The Availability Of Pictorial Depth Cuesmentioning
confidence: 99%
“…As was mentioned, luminance contrast was also investigated and reported in the literature [ 45 ]. While we did not investigate it, we examined light location and color.…”
Section: Discussionmentioning
confidence: 99%
“…It was also examined whether the existence of virtual avatars can affect distance estimation [ 42 , 43 , 44 ]. Luminance contrast can influence it as well [ 45 ]. Ground information also plays a critical role [ 46 ]: horizontal, vertical lines, or even brick textures can affect distance estimation [ 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…We refer the reader to the survey by Renner et al [61] for an in-depth review on the topic. The significant variability of available pictorial depth cues-such as texture [71], lighting [70], number of objects [38]-in different virtual environments could cause varying levels of distortion in perceived depth. The technical properties of current VR systems, such as FoV [35], IPD [4,78], and vergence-accommodation conflict [27] may also affect depth perception accuracy.…”
Section: Perception Studies In Immersive Vrmentioning
confidence: 99%